Needs Analysis of Teacher Administration Based on Google Sites in Elementary Schools - Susnita, Deka; Jaenudin, Riswan; Syarifuddin, Syarifuddin (Journal of Educational Sciences, 2024)
This research aims to analyze the administrative needs of teachers in elementary schools. At this stage the researcher made observations of several elementary school teachers in Jejawi District regarding the administration carried out so far. Interviews were conducted during testing with teacher representatives to find out what needed to be improved before the validation instrument was used. Data collection in this research used qualitative data. Analysis techniques in qualitative research focus more on the details of understanding a problem in depth rather than on the problem as a generalized subject of study. The data that researchers need to analyze is the use of Google Sites as an online service that makes it easier for teachers to more practically download teacher administration created by researchers in one link. Based on observations of teachers who carry out administration manually, only 24% of teachers complete administration. This research is expected to increase the administrative work of teachers in elementary schools by up to 100%. Thus, it can be concluded that this analysis of teacher administration needs is useful for designing and building a Google Sites-based teacher administration system so that teachers can easily manage elementary school teacher administration.